Prevalence of Transfusion Transmitted Virus Infection in Hemodialysis Patients and Injection Drug Users Compared to Healthy Blood Donors in Isfahan, Iran - Behrooz Ataei; Alireza Emami Naeini; Farzin Khorvash; Mohammad Reza Yazdani; Abbas-Ali Javadi (Gastroenterology Research and Practice)
Introduction. The pathogenicity and transmission routes of Transfusion Transmitted Virus (TTV) remain unclear. The aim of this study was to determine the prevalence of TTV in hemodialysis patients, injecting drug users (IDUs), and healthy blood donors, in Isfahan, Iran. Method. In a case-control study, a total of 108 subjects were put into three groups namely Group I, 36 hemodialysis patients; Group II, 36 IDUs; and Group III, 36 healthy blood donors as the control group. A 5 ml blood sample was collected from each subject in an EDTA-containing tube. Samples were tested for TTV DNA by means of real-time polymerase chain reaction (PCR). Results. The mean age was years. Seventy-one subjects (66%) were male. Of the108 cases, 30 (27.8%) were TTV positive and 78 (72.2%) were TTV negative. The prevalence of TTV in IDUs [21 (58%)] was significantly higher than in the other groups [group I: 6 (17 %) and group III: 3 (8%)] (). Conclusion. The prevalence of TTV in IDUs is significantly higher than in both hemodialysis patients and general population in Isfahan, Iran. It seems necessary to take serious measures to reduce the risk of TTV transmission to IDUs’ close contacts and health care providers.